1991
DOI: 10.1164/ajrccm/144.6.1274
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Late Airway Response of Allergic Rhinitis Patients to Segmental Antigen Challenge: Characterization of Eosinophil and Mast Cell Mediators

Abstract: Segmental antigen bronchoprovocation was used to define the nature of the inflammatory process in allergic airway disease. Bronchoalveolar lavage fluid obtained from allergic rhinitis patients 12 min after segmental antigen instillation (immediate response) revealed a significant increase in histamine and tryptase, but no cellular response. Repeat segmental lavage 48 h later (late response) showed marked and significant increases in both low and normal density eosinophils as well as striking elevations of eosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
130
0
2

Year Published

1995
1995
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 270 publications
(141 citation statements)
references
References 15 publications
9
130
0
2
Order By: Relevance
“…Previous studies involving allergic rhinitis and asthma patients have shown a significant increase in IL-5 concentrations in BALF after SBP (11,27,28). We could also demonstrate an increased expression of both IL-5 and eotaxin in the bronchial mucosa of allergic patients 24 h after SBP.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Previous studies involving allergic rhinitis and asthma patients have shown a significant increase in IL-5 concentrations in BALF after SBP (11,27,28). We could also demonstrate an increased expression of both IL-5 and eotaxin in the bronchial mucosa of allergic patients 24 h after SBP.…”
Section: Discussionsupporting
confidence: 70%
“…Generalized pulmonary inflammation cannot be explained by bronchoscopic and biopsy findings, per se (21). To minimize intraluminal spread of antigen from the allergenchallenged bronchial segment to other segments, we held the bronchoscope in the wedged position for 5 min, as has been suggested by other authors (11). It is also very unlikely that allergen spilled into the nose after SBP, since we performed bronchoscopy by the oral route, and it did not lead to excessive coughing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that enhanced LTC 4 production is closely related to the pathophysiology of asthma attacks. These results are consistent with a report that showed enhanced LTC 4 production by activated eosinophils during antigen challenge [19]. In addition, SCHAUER et al [20] showed that, upon stimulation with the ionophore A23187, the granulocytes of asthmatic children generated significantly more LTC 4 than those of healthy controls.…”
Section: Discussionsupporting
confidence: 91%
“…The gene cluster for IL-3, IL-4, IL-5 and GM-CSF is expressed by bronchoalveolar T lymphocytes in patients with atopic asthma [22], and mRNA for IL-5 has been detected in bronchial tissue biopsies of patients with asthma [23]. In previous studies, IL-5 and, in some cases, GM-CSF and/or IL-3 were detected in BALF from patients with allergic rhinitis who underwent segmental bronchoprovocation with ragweed extract [24,25]. Significant elevations of tumour necrosis factor (TNF), GM-CSF, IL-1 , IL-2, and IL-6 were detected by immunoassay (GM-CSF, IL-1 and IL-6), bioassay (TNF and IL-6), and polymerase chain reaction (PCR) (IL-1 and TNF) in the airways of patients with symptomatic asthma compared with that of patients with asymptomatic asthma [26].…”
Section: Introductionmentioning
confidence: 93%